Targeting ASK1 by CS17919 alleviates kidney‐ and liver‐related diseases in murine models - Guoqiang Liao; Qianjiao Yang; Xuhua Mao; Yiru Zhao; Beizhong Chen; Kun Zhang; Yu Zhang; Ping Zhang; Zhengli Chen; Shengjian Huang (Animal Models and Experimental Medicine)
Abstract Background Apoptosis signal‐regulating kinase 1 (ASK1) is a MAP3K kinase in the MAPK signaling pathway activated by stressors and triggers downstream biological effects such as inflammation and apoptosis; therefore, inhibition of ASK1 kinase activity can protect cells from pathological injury. In this study, we designed and synthesized a novel selective ASK1 inhibitor, CS17919, and investigated its pharmacological effects in various animal models of metabolic injury. Methods First, we validated the ability of CS17919 to inhibit ASK1 in vitro and then tested the safety profile of CS17919 in cell lines compared with Selonsertib (GS‐4997), a phase III ASK1 inhibitor. We then conducted pharmacokinetic (PK) studies in mice. Finally, we tested the in vivo efficacy of CS17919 in murine models of chronic kidney disease (CKD) and non‐alcoholic steatohepatitis (NASH). Results Compared to GS‐4997, CS17919 demonstrated comparable inhibition of ASK1 in vitro, exhibited lower toxicity, and provided greater protection in palmitic acid‐treated LO2 cells. CS17919 also showed pronounced pharmacokinetic properties such as a high plasma concentration. In the unilateral ureteral obstruction model (UUO), CS17919 and GS‐4997 preserved kidney function and showed a non‐significant tendency to alleviate kidney fibrosis. In the diabetic kidney disease (DKD) model, CS17919 significantly improved serum creatinine and glomerular sclerosis. In the NASH model, the combination of CS17919 and a THRβ agonist (CS27109) was found to significantly improve liver inflammation and substantially reduced liver fibrosis. Conclusions CS17919 showed cell protective, anti‐inflammatory, and antifibrotic effects in vitro and in vivo, suggesting its therapeutic potential for metabolic‐related kidney and liver diseases.